Investigation of hydrolysis and condensation of methyltriethoxysilane in aqueous systems - Kurjata, Jan; Rozga-Wijas, Krystyna; Stanczyk, Wlodzimierz (European Journal of Chemistry, 2013)
An effective synthesis of methylethoxysilanes and emulsification of methyltriethoxysilane is described. Hydrolysis and condensation products of methyltriethoxysilane were identified and studied using 29Si NMR, mass spectrometry and infrared spectroscopy. The presented analyses are important from practical point of view, as the emulsion in question is used for hydrophobization of building materials and soil. The most striking finding is high stability of the low molecular products of hydrolysis - methylsilanetriol [MeSi(OH)3] and its dimer [(OH)2(Me)SiOSi(Me)(OH)2]. All of which were still present in the aqueous medium, after 40 days of storage at ambient conditions. This finding suggests that condensation processes leading to the formation of polymer network are slow in the emulsion and a large number of reactive hydroxyl groups are present in the system allowing for the effective hydrophobization of mineral material.